Effect of 17 beta-estradiol and alendronate on the removal torque of osseointegrated titanium implants in ovariectomized rats - Giro, Gabriela; Sakakura, Celso Eduardo; Alves, Daniela Goni; Pereira, Rosa M. R.; Marcantonio, Elcio; Orrico, Silvana Regina Perez [UNESP] (Amer Acad Periodontology, 2007)
Background: This study investigated the influence of estrogen deficiency and its treatment with estrogen and alendronate on the removal torque of osseointegrated titanium implants.Methods: Fifty-eight female Wistar rats received a titanium implant in the tibia metaphysis. After 60 days, which was needed for implant osseointegration, the animals were randomly divided into five groups: control (CTLE; N = 10), sham surgery (SHAM; N = 12), ovariectomy (OVX; N = 12), ovariectomy followed by hormone replacement (EST; N = 12), and ovariectomy followed by treatment with alendronate (ALE; N = 12). The CTLE group was sacrificed to confirm osseointegration, whereas the remaining groups were submitted to sham surgery or ovariectomy according to their designations. After 90 days, these animals were also sacrificed. Densitometry of femur and lumbar vertebrae was performed by dual-energy x-ray absorptiometry (DXA) to confirm systemic impairment of the animals. All implants were subjected to removal torque.Results: Densitometric analysis of the femur and lumbar vertebrae confirmed a systemic impairment of the animals, disclosing lower values of bone mineral density for OVX. Analysis of the removal torque of the implants showed statistically lower values (P <0.05) for the OVX group in relation to the other groups. However, the group treated with alendronate (ALE group) presented significantly higher torque values compared to the others.Conclusion: According to this study, estrogen deficiency was observed to have a negative influence on the removal torque of osseointegrated implants, whereas treatment with alendronate
Keywords: dental implants; estrogen replacement therapy; osteoporosis; ovariectomy; rats